Amorphous FeCrNi/a-C:H coatings with self-organizednanotubular structure. (15th July 2017) - Suszko, Tomasz; Gulbiński, Witold; Morgiel, Jerzy; Greczynski, Grzesgorz; Dobruchowska, Ewa; Dłużewski, Piotr; Lu, Jun; Hultman, Lars
Abstract: Amorphous FeCrNi/a-C:H coatings are deposited by pulsed magnetron sputtering of austenitic stainless steel in argon/acetylene atmosphere. High-resolution transmission electron microscopy, electron energy loss spectroscopy and energy dispersive X-ray mapping reveal a pronounced nanotubular structure consisting of metallic cores that thread along the film growth direction and are encapsulated by amorphous carbon shells in a cream-roll fashion. The coatings exhibit excellent mechanical, tribological, and anti-corrosion properties. Graphical Abstract: